Istota i rozwój filozofii szwajcarskiej = Sušnost` i stanovlenie švejcarskoj filosofii - Tumarkin, Anna Pavlovna (1875-1951) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book is extremely valuable, presenting the work of Anna Tumarkin - a Russian thinker, the first woman professor of philosophy, whose name and work rarely appear in textbooks on the history of philosophy. The work is part of a series of intellectual portraits of women philosophers, which Lilianna Kiejzik has been discovering for years for a wider circle of readers of philosophical literature. It is a passionate introduction to the little-known history of Swiss philosophy.
Keywords: Tumarkin, Anna Pavlovna (1875-1951); filozofia szwajcarska - historia; historia filozofii; history of philosophy; history of Swiss philosophy